1995
DOI: 10.1111/j.1365-2362.1995.tb01545.x
|View full text |Cite
|
Sign up to set email alerts
|

Hyperhomocysteinaemia and endothelial dysfunction in young patients with peripheral arterial occlusive disease

Abstract: Abstract. Hyperhomocysteinaemia, defined as an abnormally high plasma homocysteine concentration after an oral methionine load, is common in young ( ^ 50 years) patients with peripheral arterial occlusive disease. It is thought to predispose to atherosclerosis by injuring the vascular endothelium. Treatment with pyridoxine and/or folic acid may lower plasma homo cysteine levels, In mildly hyperhomocysteinaemic patients with peripheral arterial occlusive disease, we studied the effect of daily treatment with py… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 188 publications
(10 citation statements)
references
References 28 publications
2
8
0
Order By: Relevance
“…Accordingly, it is reasonable to suggest that patients with hyperthyroidism experience endothelial cell dysfunction. On the other hand, although our ®ndings of decreased basal t-PA levels in plasma in patients with endothelial dysfunction are in accordance with those obtained by some investigators [8,20,21], contradictory results have been reported in different diseases by others [9,10,19]. The reasons for the contradiction are not clear.…”
Section: Discussionsupporting
confidence: 77%
“…Accordingly, it is reasonable to suggest that patients with hyperthyroidism experience endothelial cell dysfunction. On the other hand, although our ®ndings of decreased basal t-PA levels in plasma in patients with endothelial dysfunction are in accordance with those obtained by some investigators [8,20,21], contradictory results have been reported in different diseases by others [9,10,19]. The reasons for the contradiction are not clear.…”
Section: Discussionsupporting
confidence: 77%
“…In our study, the plasma level of homocysteine was significantly higher in patients with Buerger’s disease as compared to atherosclerosis and healthy cases before treatment. (p < 0.001) The higher values of plasma homocysteine levels in Buerger’s disease patients and simultaneously the higher prevalence of tobacco usage in this group (90.9% of cases) and also higher plasma levels of homocysteine in smoker cases of 3 groups was compared to the initial measurement in all patients, suggests that tobacco could be the principle cause of hyperhomocysteinemia in such patients, which also has been revealed in other studies (4, 6, 12, 14). The effect of folic acid therapy on elevated homocysteine levels in some medical conditions has been evaluated in a variety of studies.…”
Section: Discussionsupporting
confidence: 76%
“…Homocysteine can build up in the arteries, which may increase the risk of blood clots, heart attack, and stroke. Vitamin B 6, B12, and folic acid are essential for reducing total homocysteine and reverse endothelial dysfunction induced by high total homocysteine levels [ 8 - 9 ]. In a few prospective studies, total homocysteine levels >10.2µmol/L were found to be associated with the doubling of vascular risk, whereas >20µmol/L was associated with an eight to nine-fold increase in vascular risk [ 10 ].…”
Section: Introductionmentioning
confidence: 99%